Covid-19 and Chronic Diseases - Salem, Hajer (faculty of applied basic medical science - Libyan international medical university, 2022)
The causative pathogen for the covid-19 first emerged in China, in December 2019, and by March 2020, it was declared a global pandemic.
Keywords: covid-19